Software engineering and knowledge engineering: theory and practice : Volume 2 - Wu, Yanwen (Advances in intelligent and soft computing, 2012)
The volume includes a set of selected papers extended and revised from the I2009 Pacific-Asia Conference on Knowledge Engineering and Software Engineering (KESE 2009) was held on December 19~ 20, 2009, Shenzhen, China.   Volume 2 is to provide a forum for researchers, educators, engineers, and government officials involved in the general areas of Knowledge Engineering and Communication Technology to disseminate their latest research results and exchange views on the future research directions of these fields. 135 high-quality papers are included in the volume. Each paper has been peer-reviewed by at least 2 program committee members and selected by the volume editor Prof.Yanwen Wu.   On behalf of the this volume, we would like to express our sincere appreciation to all of authors and referees for their efforts reviewing the papers. Hoping you can find lots of profound research ideas and results on the related fields of Knowledge Engineering and Communication Technology.